Anxiety and the Face of the Other: Tillich and Levinas on the Origin of Questioning - Dickman, Nathan Eric (Sophia, 2009)
With almost a century of historical distance between Heidegger’s retrieval of the question of being and contemporary concern about the Other, we have accrued invaluable experiences for critical leverage about what it is to ask one another questions. I offer a sketch aimed at adapting Tillich’s theological system grounded in existential questioning to today by juxtaposing him with Levinas’ philosophical ethics. Tillich and Levinas provide motive for reflection on the topic of questioning in particular. In the case of Tillich, questions constitute a crucial moment in the dialogue between our contemporary existential situation and religious symbols, or in what he called the ‘method of correlation.’ Furthermore, Tillich locates in the very structure of questioning the germ of our participation in our essential nature despite existential disruption. Beneath his more provocative and prophetic discourse on the absolute desolation and height of the Other, Levinas sees in questions a different kind of possibility. It is not our essential and existential selves, but oneself and the absolutely Other who come together in the question yet retain their infinite difference. Heidegger is the immediate predecessor from whom both Tillich and Levinas inherit a predilection for reflection on questioning. What is at stake is not merely the legacy of Heidegger’s construal of questioning, but, more importantly here, the fundamental sources Tillich and Levinas posit as the origin of our questioning.